PENDEKATAN ALTERNATIF DALAM PELAKSANAAN SUPERVISI PENGAJARAN - Imam Gunawan (Universitas PGRI Madiun, 2011)
Teaching supervision may aim to create a better learning atmosphere, guide teachers’ teaching experience, and help the teacher assess their students. A supervisor motivation to teachers can improve their commitment. There are approaches to supervision and dimensions to classify teachers to help supervisors select the approach to adopt. Among the approaches are the clinic, directive, non-directive, collaborative, informal, collegial, and individual related to teacher dimensions such as extent of attention, responsibility, maturity, and cognitive complexity of the teachers which ease to choose recommended approaches to apply in the supervising.